Ecological Interstate Systems as an Object of Legal Research - Yergobek, Shynggys K.; Atakhanova, Saltanat K.; Altayeva, Kamilya Zh.; Nyssanbekova, Lyazzat B.; Umbetbayeva, Zhuldyz B. (Journal of Environmental Accounting and Management, 2026)
The paper shows that the management and regulation of transboundary natural resources is carried out in most states from the point of view of the economic approach. At the same time, the requirements of ecological systems speak about the need to consider natural and territorial complexes as unified mechanisms that cannot be considered separately, but only in combination and in conjunction with each component that make up this ecological system. The authors show that such a perception of ecological systems inevitably leads to the fact that the issue of their safety appears in the framework of cooperation between two or more states. The subject of the study is environmental systems as an element of governance in the framework of supranational and interstate agreements. They are considered as an aggregate of natural resources and biological elements living in a given territory. The novelty of the study is the provision that the management of an ecological system in the territory of two or more states requires the development of not only global standards for the use and protection of ecological systems, but also to determine the feasibility of implementing management and economic cooperation mechanisms for the even development of transboundary ecological systems. Directions for further research are the possibility of organizing supranational regulatory documents that will allow the allocation of shared environmental systems and determine the possibility of the territories’ even development.